Предмет: Алгебра,
автор: Аноним
Решите уравнение пожалуйста !
Приложения:
Ответы
Автор ответа:
0
p-3+(2-3p)(-2p-3)=-(1-6p)(p+1);
p-3+(-4p+6p²-6+9p)=-(p-6p²+1-6p);
p-3-4p+6p²-6+9p=-p+6p²-1+6p;
p-3-4p+6p²-6+9p+p-6p²+1-6p=0;
0·p²+p-8=0;
p=8.
О т в е т. p=8
p-3+(-4p+6p²-6+9p)=-(p-6p²+1-6p);
p-3-4p+6p²-6+9p=-p+6p²-1+6p;
p-3-4p+6p²-6+9p+p-6p²+1-6p=0;
0·p²+p-8=0;
p=8.
О т в е т. p=8
Похожие вопросы
Предмет: Математика,
автор: cubviktoria741
Предмет: География,
автор: sofiiaguseinova166
Предмет: Русский язык,
автор: gleblavrinenko10
Предмет: Физика,
автор: Darkassasin52
Предмет: Физика,
автор: bsmiam18